Characteristics and Reservoir Evaluation of Dolomite in the Qixia Formation at the Lao Gongqiao Village Profile, Huaying Mountain - Liu, Yihong (International Journal of Natural Resources and Environmental Studies, 2025)
This study focuses on the dolomite in the Lao Gongqiao Village profile in the Huaying Mountain. By analyzing field outcrops and thin sections, two types of dolomite occurrences were identified: fine-crystalline dolomite at the bottom of the Qixia Formation and spotted dolomitic limestone in the middle to upper part of the formation. The profile also features saddle-shaped dolomitic cement. The fine-crystalline dolomite has primary porosity mainly in the form of intercrystalline (dissolution) pores, with moderate porosity and low permeability. The spotted dolomitic limestone, with limited dolomitization, has poor reservoir properties. The saddle-shaped dolomite, a later cement, reduces the reservoir space, leading to poorer reservoir performance.